Microbes and the mind: emerging hallmarks of the gut microbiota–brain axis. (31st March 2016) - Bauer, Kylynda C.; Huus, Kelsey E.; Finlay, B. Brett
Summary: The concept of a gut microbiota–brain axis has emerged to describe the complex and continuous signalling between the gut microbiota and host nervous system. This review examines key microbial‐derived neuromodulators and structural components that comprise the gut microbiota–brain axis. To conclude, we briefly identify current challenges in gut microbiota–brain research and suggest a framework to characterize these interactions. Here, we propose five emerging hallmarks of the gut microbiota–brain axis: (i) Indistinguishability, (ii) Emergence, (iii) Bidirectional Signalling, (iv) Critical Window Fluidity and (5) Neural Homeostasis.